Efeito dos taninos condensados de forrageiras nativas do semi-árido nordestino sobre o crescimento e atividade celulolítica de Ruminococcus flavefaciens FD1 - Guimarães-Beelen, P.M.; Berchielli, Telma Teresinha [UNESP]; Buddington, R.; Beelen, R. (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2006)
Avaliaram-se o crescimento da população, a atividade in vitro da enzima 1,4-b-endoglucanase e a taxa de digestão de celulose em culturas de Ruminococcus flavefaciens FD1 na presença de 50, 100, 200 e 400µg/ml de taninos purificado das leguminosas Mimosa hostilis (Jurema Preta), Mimosa caesalpinifolia (Sabiá) e Bauhinia cheilantha (Mororó). O crescimento bacteriano, a atividade da endoglucanase e a digestão de celulose foram fortemente inibidos pela presença dos taninos condensados purificados das três espécies, entretanto, a intensidade da inibição foi variável em função da espécie da leguminosa e da concentração de tanino.

The effects of tannin levels in three Brazilian browse legumes Mimosa hostilis (Jurema Preta), Mimosa caesalpinifolia (Sabiá) e Bauhinia cheilantha (Mororó) on growth and endoglucanase activity of Ruminococcus flavefaciens FD1 were evaluated. Isolated cultures of Ruminococcus flavefaciens FD1 were used to assess cellular growth, 1, 4-beta-endoglucanase activity, and cellulose digestion in the presence of 50, 100, 200 and 400µg/ml of purified tannins from the three legume species. Growth of FD1, 1, 4-beta-endoglucanase activity and cellulose digestion were highly inhibited by the presence of purified tannins of the three legume species. However, the intensity of inhibition varied in according to the legume species and tannin concentration.
Effects of condensed tannins from northeastern semi-arid shrubs on growth and cellulolytic activity of Ruminococcus flavefaciens FD1
Keywords: Rumen; cellulose digestion; Cellulase; ruminal bacteria; proantocyanidin; Rúmen; atividade celulolítica; Celulase; bacteria proantocianidina